PENILAIAN HEDONIK DAN PERILAKU KONSUMEN TERHADAP SNACK YANG DIFORTIFIKASI TEPUNG CANGKANG KERANG SIMPING (Amusium sp.) - Susana E. Ratnawati; Tri W. Agustini; Johannes Hutabarat (Universitas Gadjah Mada, 2014)
Scallop shells ﬂ our need to be formulated with a source of phosphor. The aim of this study was to examine the formulation of calcium and phosphorus scallop shells ﬂ our with corn and millet and its inﬂ uence on the level of snacks preference and to identify the potential marketing. This research methods is experimental laboratories and descriptive using completely randomized design (CRD) by three treatments with three replications. The treatment is the addition of ﬂ our calcium products, include the control 0% (A1, A2, A3), the addition of scallop shells ﬂ our with corn ﬂ our (B1, B2, B3) and the addition of ﬂ our shell scallop shells with millet ﬂ our (C1, C2, C3). Parameters observed include calcium, phosphor and hedonic value. Hedonic value is tested using Kruskal Wallis analysis. In the results show that the results of fortiﬁ ed snacks produce calcium and phosphorus ratio close to 3 : 1 (Ca / P), however cookies with scallop shells and millet ﬂ our fortiﬁ cation provide calcium and phosphorus ratio of 12.3: 1 (Ca / P). Extrudates with scallop shells and corn ﬂ our fortiﬁ cation is the closest to the ratio of calcium and phosphorus balance, with 3.2 : 1 (Ca / P) ratio and has the highest hedonic value (6.89 ≤ μ ≤ 7.57). On consumer behavior assessment concluded that the potential customers in Semarang is as much as 86.7% who liked the product and interested to products. The suitable prices for 30 grams products of extrudates that fortiﬁ ed with scallop shells and corn ﬂ our is Rp. 3.600, -.